Snake Venom Pharmacokinetics and Acute Toxic Outcomes Following Daboia siamensis Envenoming: Experimental and Clinical Correlations - Sethapong Lertsakulbunlue; Wipapan Khimmaktong; Orawan Khow; Wittawat Chantkran; Jureeporn Noiphrom; Kanyanat Promruangreang; Lawan Chanhome; Janeyuth Chaisakul (Toxins)
An understanding of snake venom pharmacokinetics is essential for determining clinical outcomes of envenoming and developing therapeutic approaches to the treatment of envenoming, especially regarding the timing and optimal dosage of antivenom administration. Daboia siamensis (Eastern Russell’s viper) envenoming causes systemic coagulopathy and severe hemorrhage including acute kidney injury. These toxic outcomes can be diminished by the administration of high quantities of Russell’s viper antivenom. This study aimed to determine the correlation between the clinical profiles of D. siamensis envenomed patients and experimental data by measuring plasma venom concentration and conducting histopathological analyses of heart, kidney, and liver tissues in rats 6 h after experimental D. siamensis envenomation. Intramuscular (i.m.) administration of D. siamensis venom to anesthetized rats (200 µg/kg) resulted in a rapid absorption of venom which reached a peak concentration at 60 min before declining and then plateauing. Urine samples detected 209.3 ± 21.6 ng/mL of D. siamensis venom following i.m. administration at 6 h. Histopathological studies showed morphological changes in heart, kidney, and liver tissues following 3 h experimental envenoming and exhibited a higher degree of severity at 6 h. A retrospective study of the clinical profile and laboratory examination of Russell’s viper envenomed patients in Central Thailand was also evaluated, showing that systemic coagulopathy and local effects were commonly observed in the early stage of D. siamensis envenoming. An abnormal increase in creatinine levels was found in 13.6% of the population. Early administration of specific antivenom within 1–2 h following envenoming is highly recommended to prevent life-threatening outcomes such as severe coagulation and acute kidney injury.